2017
DOI: 10.1037/prj0000236
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric versus physical disabilities: A comparison of barriers and facilitators to employment.

Abstract: VR counselors should be aware that although most applicants with psychiatric disabilities place a great deal of importance on being employed, they face additional barriers to employment. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…In comparison with people with physical disabilities, PMIs have longer periods of non-employment and are more likely to report non-health reasons as barriers to employment, such as lack of skills and getting fired from the job. 27 The RPWD Act, 2016, in section 3(5), directs the government to take the necessary steps to ensure RA and, in section 20(2), emphasizes that RA be provided in government establishments. As per the Act, denial of RA is tantamount to discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with people with physical disabilities, PMIs have longer periods of non-employment and are more likely to report non-health reasons as barriers to employment, such as lack of skills and getting fired from the job. 27 The RPWD Act, 2016, in section 3(5), directs the government to take the necessary steps to ensure RA and, in section 20(2), emphasizes that RA be provided in government establishments. As per the Act, denial of RA is tantamount to discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…The topic list was designed with the research group using topics from previous studies in employment and mental health in general [32,45,46]. The following topics were discussed: experiences with employment, barriers and facilitators to employment, stigma and disclosure of BPD (see S1 File).…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that receipt of workplace accommodations is associated with better employment outcomes (Burkhauser et al 1995;Chow 2012;Cook et al 2015). Among VR applicants with psychiatric disabilities, accommodations such as flexible schedules and modified work duties were positively correlated with continued employment (Sevak and Khan 2017). Among workers nearing retirement age with a new onset of disability, receipt of accommodations is associated with delayed labor force exit over a 2-year period, though not over a longer period (Hill et al 2016).…”
Section: Introductionmentioning
confidence: 99%